Digital Natives Disconnected. The Qualitative Research on Mediatized Life of Polish and International Students in Rzeszow and Warsaw, Poland - Leonowicz-Bukała, Iwona; Martens, Anna; Przywara, Barbara (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
Studies on the mediatization of everyday life are becoming more and more important in the area of media and communication studies in the Western scientific literature. The main questions of these analyses concern the range of this phenomenon and the possible consequences for the social, cultural and psychological life of societies and individuals. Using this approach, the authors of this paper present the results of a qualitative study based on the social experiment #NoWeb (#BezSieci), conducted on the population of 184 students of two Polish universities. For 7 days, the participants of the experiment tried to live offline, which means not using the Internet at all, and writing down their experiences in paper diaries. Only 8 of them were able to live offline until the last day of the project. The main research results of the study show that almost all areas of living are dependant and supported by online access, which has a strong influence on the capability to act offline among young adults. Lacking access to the Internet, the participants of the study were very often unable to deal with simple tasks. At the same time, the experiences of staying offline enabled them to discover new possibilities of everyday functioning and effective use of additional free time with benefits for their well-being and interpersonal relations.